(untitled) (Journal of the College of Basic Education, 2022)
The aim of this research is to idenfify the level of admistrative empowerment and its relationship to enhancing the creative abilities of Karkh education employees in Baghdad in view of some variables (gender,educational qualification,occupational category,and years of experience). Aquestionnaire of (57) paragraph was applied to asample of (120) male and female employees selected by acomprehensive survey method. The questionnaire was characterized by high reliability and validity coefficients where Cronbach’s alpha coefficient (0.94) was used , and after collection and analysis of data , It was found that the arithmetic mean of the total field was (3.96), with a standard deviation of (0.39), and it was found that the senior management in the General Directorate of Karkh Education is working hard to enhance the creative abilities of its employees. The arithmetic average has reached for the domain (3.89) with a standard deviation of (0.37) and a significant response degree.It was found a direct statistically significant relationship between the reality of administrative empowerment followed in the General Directorate of Karkh Education and the enhancement of the creative abilities of its employees.The researcher recommended The need for the senior management in Karkh education to work hard to create an atmosphere help to implement the concept of employee empowerment by deepening the concept of employee participation in making decisions related to their work.